Environmental militarism: Burma's extractive industries - Matthew Smith (2018)
Natural gas projects in Burma have resulted in human rights abuses and environmental degradation, exposed by two high-profile lawsuits brought by ethnic villagers against Unocal Corporation and Total. These cases are important for the future of holding non-state actors accountable for human rights abuses and for the future of corporate social responsibility (CSR), but positive and measurable impacts are not yet evident in Burma. This is due in part to the irresponsible nature of the Asian corporations that are competing for Burma's resources and in part to the unchanged nature of the military junta, which violates human rights while practising what can be called environmental militarism, i.e. strengthening the armed forces vis-à-vis exploitation and trade of natural resources. This paper concludes that large-scale extractive projects in Burma should be avoided until appropriate preconditions for responsible investment are in place.